The Role of Prophylactic Tamsulosin in Preventing Postoperative Urinary Retention Following Surgery under Spinal Anaesthesia - Tanveer Sadiq Ch, Ghulam Mustafa, Nimra Usman, Faisal Toheed, Sara Khalid Memon, Sana Atiq-Ur-Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Postoperative urinary retention (POUR) is a common complication following surgery under spinal anesthesia, often leading to prolonged catheterization, increased risk of infections, and extended hospital stays. Objective: To evaluate the effectiveness of prophylactic tamsulosin in preventing POUR in patients undergoing elective surgery under spinal anesthesia. Study Design: Prospective observational study Place and Duration of Study: Mohtarma Benazir Bhutto Shaheed Medical College Mirpur AJK from 1st January 2023 to 31st July 2023. Methodology: Two hundred and twenty five patients scheduled for elective surgery under spinal anaesthesia were enrolled. Data were collected prospectively using a standardized case report form. Demographic details, surgical and anaesthetic parameters, and postoperative outcomes were recorded. Results: The incidence of POUR was significantly lower in the tamsulosin group (10.7%) compared to the placebo group (24.8%) (p=0.004). Patients in the tamsulosin group had a shorter time to first void (3.2±1.1 hours vs. 5.8±2.3 hours, p<0.001) and a reduced need for catheterization (8.9% vs. 22.1%, p=0.006). The mean length of hospital stay was also shorter in the tamsulosin group (2.5±0.8 days vs 3.2±1.1 days, p=0.002). Tamsulosin was well-tolerated, with no serious adverse events reported. Conclusion: Prophylactic tamsulosin significantly reduces the incidence of POUR, shortens the time to first void, decreases the need for catheterization, and is associated with a shorter hospital stay in patients undergoing surgery under spinal anaesthesia. Keywords: Prophylactic tamsulosin, Elective Surgery, Spinal anesthesia, Postoperative urinary retention